Investigation and optimization of optical and electric properties of indium-tin oxide films obtained by magnetron sputtering method at different oxygen flows - Zholdybaev, K.S.; Kundyzbai, D.K.; Aimaganbetov, K.P.; Shongalova, A.K.; Zhantuarov, S.R.; Ongar, I.A.; Tokmoldin, N.S. (Recent Contributions to Physics, 2020)
Indium tin oxide is a widely used material in modern optics and electronics and has a wide range of applications from antireflection coatings to liquid crystal displays. This work is devoted to the use of indium tin oxide films in the field of solar energy. Films were obtained using magnetron sputtering, using the PVD (physical vapour deposition) method. The optimization of film synthesis modes is one of the most important tasks for solar photovoltaic. In this paper, we show the results of studying the influence of oxygen fluxes during the synthesis on a glass of indium-tin oxide films obtained by magnetron sputtering, as well as the effect of the thicknesses of the obtained films on their optical and electrical properties. Optical properties are presented as transmission spectra. Electrical properties are presented in the form of results of measurements of resistivity, mobility and concentration of carriers and their relationship with the speed of movement of the samples, the thickness and flow of oxygen. It was found that the characteristics of indium-tin oxide films depend on oxygen fluxes, as well as on the thickness of the films themselves. Annealing of films at a temperature of 300 ° C was chosen as optimization of the technological process.